An innovative fixture for testing the crashworthiness of composite materials (Fracture and Structural Integrity, 2020)
Despite the growing diffusion of composite materials in automotive and aerospace sectors, a standard procedure for testing their crashworthiness has not been developed yet. At present, the international standards for testing composite materials under impact conditions are not adequate to test their crush behavior.In this paper, a procedure for measuring the energy absorption due to the compressive crushing of a composite flat specimen, along its mid plane, is proposed. The experimental setup requires a fixture to hold the specimen and to avoid its buckling and an instrumented drop weight tower to obtain the force-displacement curves with the aim of calculating the Specific Energy Absorption.The paper will describe the adopted test procedure and some of the features of the newly developed experimental setup. The effectiveness of the procedure is demonstrated by testing several glass fiber-epoxy specimens under different impact energies.
Keywords: Crashworthiness; Specific Energy Absorption; impact response